TAF Effect on Liquidity Risk Exposure - Stefano Puddu; Andreas Waelchli (University of Neuchâtel, Institute of Economic Research (IRENE), 2015)
Using a unique bank-level dataset, we assess the impact of the Term Auction Facility program on bank liquidity risk. The change in the US housing price index at state levels between 2002:Q1 and 2006:Q3 is the exclusion restriction to control for potential selection bias. On average, TAF banks exhibit higher ex ante levels of liquidity risk and they drastically reduce funding liquidity risk in the periods after the rst time they received TAF funds. TAF banks show larger reductions in liquidity and they are more likely to be headquartered in US states that experienced sharper housing price appreciation before 2007.
Keywords: G21; G28; G32; 330; Term Auction Facility; Liquidity Risk; Financial Crisis; Unconventional Monetary Policies